Latin America and the Social Contract : Patterns of Social Spending and Taxation - Breceda, Karla; Rigolini, Jamele; Saavedra, Jaime (World Bank, Washington, DC, 2012)
This paper presents an incidence analysis of both social spending and taxation for seven Latin American countries, the United Kingdom, and the United States. The analysis shows that Latin American countries are headed de facto toward a minimalist welfare state similar to the one in the United States, rather than toward a stronger, European-like welfare state. Specifically, both in Latin America and in the United States, social spending remains fairly flat across income quintiles. On the taxation side, high income inequality causes the rich to bear most of the taxation burden. This causes a vicious cycle where the rich oppose the expansion of the welfare state (as they bear most of its burden without receiving much back), which in turn maintains long-term inequalities. The recent increased socioeconomic instability in many Latin American countries shows nonetheless a real need for a stronger welfare state, which, if unanswered, may degenerate into short-term and unsustainable policies. The case of Chile suggests that a way out from this apparent dead end can be found, as elites may be willing to raise their contribution to social spending if this can lead to a more stable social contract.